Vanitas: uma estrutura emblemática de fundo moral - Froner, Yacy-Ara (Revista de História, 1997)
This article is part of a Master's Thesis, The symbols of death and the symbolical death, which was presented in 1994 to the History Department, FFLCH/USP. Our purpose is to study two pictorical representations of the colonial period of Minas Gerais that have the same formal and conceptual structures. By means of these structures, we'll try to bring to mind the models, taking into account the age and cultural context of their production, that originated those representations.